Changes in Membrane Lipid Composition and Function Accompanying Chilling Injury in Bell Peppers. (9th November 2017) - Kong, Ximan; Wei, Baodong; Gao, Zhu; Zhou, Ying; Shi, Fei; Zhou, Xin; Zhou, Qian; Ji, Shujuan
Abstract: Bell peppers are vulnerable to low temperature (<7C) and subject to chilling injury (CI). To elucidate the relationship between cell membrane lipid composition and CI, a membrane lipidomic approach was taken. In addition, we performed microstructural analysis and low-field nuclear magnetic resonance to better understand CI. We also monitored primary physiological metabolism parameters to explain lipidomics. Our study indicated that cellular structure damage was more serious at 4C, mostly represented by damage to the plasmalemma and plastid degradation. Membrane lipidomic data analysis reveals monogalactosyldiacylglycerol, phosphatidylcholine, phosphatidylethanolamine and phosphatidic acid as crucial biomarkers during CI. Furthermore, the significant increase in proline, electrolyte leakage and phospholipase D in chilled fruits also proved that membrane lipid metabolism is involved in the response to low temperature stress. To our knowledge, this study is the first attempt to describe the CI mechanisms in bell peppers based on membrane lipidomics.